THE USE OF COMPLEMENTARY AND ALTERNATIVE THERAPIES IN CHILDHOOD CANCER: A QUESTIONNAIRE BASED ON A DESCRIPTIVE SURVEY FROM THE WESTERN BLACK SEA REGION OF TURKEY - Kurtuncu, Meltem; Yildiz, Hicran; Utas Akhan, Latife (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
The objective of this sBackground: The objective of this study was to determine what complementary and alternative therapies are used in cases ofchildhood cancer, the frequency of their use and the factors that affect the tendency to resort to these therapies.Materials and Methods: The study, of cross-sectional design, was conducted with the parents of 101 children diagnosed withcancer, using a questionnaire and the technique of face-to-face interviews. Mean scores, percentages, chi-square and Kruskal-Wallistests were used in the statistical analysis. During the study, interviews were held with 42.6% of the children's mothers and with thefathers of 44.6%.Results: The mean age of the children was 8.66±4.52 years. A group of 33.7% of the parents was making use of complementary andalternative medicine (CAM) for their children. Of the parents, 76.5% stated that CAM had been instrumental in reducing a tumor,53.8% said that their child's general condition had improved and 15.4% expressed an increase in morale. Another 41.2% concealedtheir use of CAM from their doctors and nurses. The parents that were interviewed: the age of the mother, the age of the father andthe family's economic status were determining factors in the parents' use of CAM. The prevalence of the use of CAM among parentswith children with cancer is not negligible.Conclusion: It is the researchers' belief that health professionals must be informed about the use of CAM and its methods and thatthe patients should be evaluated with an impartial approach and given information about the use of CAM, together with conventionaltreatment.tudy was to determine what complementary and alternative therapies are used in cases of childhood cancer, the frequency of their use and the factors that affect the tendency to resort to these therapies. The study, of cross-sectional design, was conducted with the parents of 101 children diagnosed with cancer, using a questionnaire and the technique of face-to-face interviews. Mean scores, percentages, chi-square and Kruskal-Wallis tests were used in the statistical analysis. During the study, interviews were held with 42.6% of the children's mothers and with the fathers of 44.6%. The mean age of the children was 8.66±4.52 years. A group of 33.7% of the parents were making use of complementary and alternative medicine (CAM) for their children. Of the parents, 76.5% stated that CAM had been instrumental in reducing a tumor, 53.8% said that their child's general condition had improved and 15.4% expressed an increase in morale. Another 41.2% concealed their use of CAM from their doctors and nurses. The parent that was interviewed, the age of the mother, the age of the father and the family's economic status were determining factors in the parents' use of CAM. The prevalence of the use of CAM among parents with children with cancer is not negligible. It is the researchers' belief that health professionals must be informed about the use of CAM and its methods and that patients should be evaluated with an impartial approach and given information about the use of CAM, together with conventional treatment.